Led source of light with high light circuit - R. R. Shiriev; A. N. Borisov; A. A. Valeev (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Consider the problems of the heat transfer process in the structural elements of the LED light source. Describe the cooling system of an LED light source using an equivalent circuit and thermal resistances. Conduct a comparative analysis of cooling systems for LED lighting devices. Perform thermodynamic calculations of the light device radiator using computer programs of automatic design systems. Suggest a way to improve the heat transfer properties of the radiator of the LED light source.METHODS. When solving the tasks set, the method of retrospective-prospective meta-analysis was used, computer programs of automatic design systems and direct determination of technical parameters using measuring instruments were used.RESULTS. The article describes the relevance of the topic, discusses the features of the heat transfer process in the structural elements of the LED light source. Thermodynamic calculations of the radiator of the lighting device were made using computer programs of automatic design systems KOMPAS and SolidWorks. The article proposes a method for improving the heat transfer properties of the radiator of an LED light source.CONCLUSION. There are many different cooling systems with their own advantages and disadvantages. The most efficient cooling systems are forced cooling systems, however, their use entails an increase in the final cost of the lighting device and a decrease in its light output due to an increase in energy consumption. Passive cooling systems are relatively cheap, but to provide effective cooling of LEDs, they must have a sufficient area of contact with the heat source, have good thermal conductivity and heat dissipation. In this case, the best way to improve the heat transfer properties of the radiator is to apply a special coating with a high heat transfer. This will increase the cooling efficiency with minimal cost without resorting to a significant change in the design features of an existing system.